Facilitating Redundancy‐Oriented Management with Gene‐Therapy‐Oriented Management Against Disaster. Issue 6 (31st December 2015) - Ha, Kyoo‐Man
Abstract : This article tests the hypothesis that "if redundancy‐oriented management has negative aspects, then it could be facilitated by gene‐therapy‐oriented management." Negative aspects include disadvantages, misjudgments, or miscalculations. The article provides a newly revised principle of disaster management by studying gene‐therapy‐oriented management. Based on qualitative analysis, redundancy‐oriented and gene‐therapy‐oriented management are analyzed via five variables: governments, business, volunteers, households, and the international community. The article is valuable because an analytical frame on gene‐therapy‐oriented management is systematically reconceptualized for the field of disaster management via three elements: unhealthy proteins (problems or failed measures), a vector (new or modified solutions), and target cells (positive outcomes). In accepting the hypothesis, the key tenet is that stakeholders have to assist the progress of redundancy‐oriented management with gene‐therapy‐oriented management by paying attention to the genes of each disaster.